7 times Deans Award Khairun Nisa was awarded the Chancellor Award - Shalfarina, Shahriman (2019)
With the rising cost of living, Khairun Nisa, 23, used to work as a part-time banquet crew at one of the hotels in Gambang during her third-year study. That was the experience of the recipient of the Chancellor’s Award at the 14th Universiti Malaysia Pahang (UMP) Convocation Ceremony.